Principles and practices of relational psychotherapy - Holmqvist, Rolf, 1948- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book provides an overview of the basic principles in relational therapy, which, in combination with the latest research about the significance of the therapeutic relationship, makes it possible to present practical therapeutic tools and techniques to help the therapist make optimal use of the interaction between patient and therapist. It presents models and concepts in relational psychotherapy that may contribute to the patient's development of relational and emotional competence, and to more authentic and meaningful ways of living with oneself and others. The book specially emphasizes the significance of the mutually constructed emotional interplay as the material for key experiences in the development of the patient - and therapist. The focus is on the usefulness of relational principles and research findings in psychotherapies of shorter duration, in primary care, psychiatric clinics, and private practice. Rich in clinical examples, Principles and Practice of Relational Psychotherapy is an extremely useful resource for psychotherapists and clinical psychologists in training and practice"--
Keywords: Interpersonal psychotherapy; Psychotherapist and patient; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health